Self-Efficacy for Oral Health Behavior among High School Female Students - Farah f. Younis, Aysen K. Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Infections and tooth loss are common side effects of mouth and dental illnesses, as can paralyzing pains and trouble eating and speaking. Another important consideration is that persistent oral infections have been linked to cardiovascular disease, diabetes, and stroke, all of which, along with other noncommunicable and chronic diseases, could be avoided by improving oral health literacy. Objectives(s): The aim of this study is to assess the self-efficacy for oral health behavior among high school female students. Methodology: This study guided by a descriptive correlational strategy. The predictive correlational design is used to predict the value of one variable based on the value of another (s) by determining the intensity and course of relationships between or among variables. This study conducted from September 20, 2021, to May 31, 2022. A non-probability convenience sample of (380) female high school students that are registered in the directorate of education. When subjects appear to be at the right place at the right time, they are used in convenience sampling research. Before the required sample size is met, researchers simply add relevant people to the study. A margin of error of 5%, a confidence level of 95%, a population size of 18.000, and a response distribution of 50% were used to establish the sample size. As a result, 377 people should be included in the sample. The total number of participants is 380. Results: There are statistically significant differences in Self-Efficacy for brushing behavior and Self-Efficacy for oral health behavior among living arrangements groups (p-value = 0.000, 0.010) respectively. Conclusion: The better the oral health value, the greater the Self-Efficacy for brushing behavior. The better the oral health value, the greater the Self-Efficacy for daily life habits. Recommendations: There is a need for the community health nurses to establish health promotion activities that target high school students; particularly the fourth graders with the goal of raising and their oral health awareness.